ZAKAT POTENTIAL AS A MEANS TO OVERCOME POVERTY (A STUDY IN LAMPUNG) - Hayati, Keumala; Caniago, Indra (Journal of Indonesian Economy and Business, 2011)
Zakat is a compulsory service run by the Muslims who are able to implement it. Zakat is a means of income redistribution and also can support development of human resources as well as enhance economic growth in Indonesia, particularly in the Lampung Province. The purposes of this study were to explore the potential of zakat and to analyze the role of zakat in empowering poor communities in Lampung Province. This research result showed that zakat potential in Lampung Province was quite large; Rp644.18 billions with the 2% opinion and Rp1.38 billions with the 4.3% opinion. Meanwhile the Regional Government of Lampung Province in 2007 and 2008, for example, budgeting for social services reached Rp29.15 billions and Rp21.01 billions respectively, including other poverty reduction programs. Therefore, zakat potential should attract the governments attention as one solution to reduce poverty in Indonesia. Zakat is not only the provision of voluntary charity, but it is an obligation that must be paid by Muslims who received the zakat obligation. The results of the analysis showed zakats potential in empowering poorcommunities in each district/city in the province of Lampung. Based on the standards meet the needs of the poor with an income of one dollar per day, from ten districts in Lampungprovince, only two districts were capable of removing the poor families from the poverty line, those are Bandar Lampung and Metro. While the potential zakat of eight otherdistricts had not been able to remove poor families from the poverty line due to the small acquisition of GDRP. This research showed that empowerment of the poor could be done based on the potentials of zakat in each district, the greater the GDRP, the greater the zakat potential that could be obtained. Even if the zakat potential was excessive than the poverty level in the district, it could be used as cross-subsidies with other districts in greater need.Keywords: Zakat Potential, poverty reduction